THE IMPLEMENTATION OF EDUCATIONAL GAME CHANGES STUDENTS’ PASSIVE CHARACTER AT NURUL JADID SENIOR HIGH SCHOOL - Islamiyah, Sohibatul; Pranata, Mohammad Sofyan Adi; Santoso, Slamet (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This classroom action research aimed to improve the activeness of students at Nurul Jadid Senior High School by implementing educational games as part of the learning process. Many students were initially passive, rarely asking questions, giving opinions, or participating in discussions. The research used a collaborative classroom action research (CAR) design with two cycles consisting of planning, acting, observing, and reflecting. Data were collected through observation, questionnaires, and documentation. The findings showed a significant improvement in students’ activeness: in the first cycle, only 45% of students actively participated, while in the second cycle, participation increased to 82%. The implementation of educational games successfully changed the students’ passive character into a more active and engaged attitude in the classroom.